Abattoir study of reproductive diseases in goats - Rahman, MH; Chowdhury, EH; Saha, SS; Islam, A; Alam, MGS (Bangladesh Veterinarian, 2010)
DOI: 10.3329/bvet.v25i2.4623 Bangl. vet. 2008. Vol. 25, No. 2, 88-91